Danlou Recipe promotes cholesterol efflux in macrophages RAW264.7 and reverses cholesterol transport in mice with hyperlipidemia induced by P407 - Wenrun Han; Dandan Zhang; Peng Zhang; Qianqian Tao; Xiaoli Du; Chunquan Yu; Pengzhi Dong; Yan Zhu (BMC, 2023)
Abstract Introduction Liver X Receptor (LXR) agonists could attenuate the development of atherosclerosis but bring excess lipid accumulation in the liver. Danlou Recipe was believed to be a benefit for improving the lipid profile. Thus, it is unclear whether Danlou Recipe could attenuate hyperlipidemia without excess lipid accumulated in the liver of mice. This study aimed to clarify if Danlou Recipe could alleviate the progression of hyperlipidemia in mice without extra lipids accumulated in the liver. Methods Male murine macrophage RAW264.7 cells and murine peritoneal macrophages were used for the in vitro experiments. Cellular cholesterol efflux was determined using the fluorescent cholesterol labeling method. Those genes involved in lipid metabolism were evaluated by qRT‐PCR and western blotting respectively. In vivo, a mouse model of hyperlipidemia induced by P407 was used to figure out the effect of Danlou Recipe on reverse cholesterol transport (RCT) and hyperlipidemia. Ethanol extract of Danlou tablet (EEDL) was prepared by extracting the whole powder of Danlou Prescription from ethanol, and the chemical composition was analyzed by ultra-performance liquid chromatography (UPLC). Results EEDL inhibits the formation of RAW264.7 macrophage-derived foam cells, and promotes ABCA1/apoA1 conducted cholesterol efflux in RAW264.7 macrophages and mouse peritoneal macrophages. In the P407-induced hyperlipidemia mouse model, oral administration of EEDL can promote RCT in vivo and improve fatty liver induced by a high-fat diet. Consistent with the findings in vitro, EEDL promotes RCT by upregulating the LXR activities. Conclusion Our results demonstrate that EEDL has the potential for targeting RCT/LXR in the treatment of lipid metabolism disorders to be developed as a safe and effective therapy.